Thirsty Energy : Modeling the Water-Energy Nexus in China - World Bank Group (World Bank, Washington, DC, 2018)
To better assess the water-energy nexus challenge in China, the Thirsty Energy initiative engaged the China Institute for Water Resources (IWHR) and Hydropower Research under the auspices of the Ministry of Water Resources and the Institute of Energy, Environment, and Economy of Tsinghua University (TU) to establish a new multiregional, water-smart energy system planning model: TIMES-ChinaW (described in chapter 6). Chapter 2 of this report provides an overview of the water-energy nexus in China, and the current water and energy picture in China are described in chapters 3 and 4. Chapter 5 describes the methodology and approach for preparing the water supply cost curves and integrating that information into the TIMES-ChinaW model. Chapter 7 explores China's future water-energy nexus using the abovementioned model and summarizes the main findings for specific water, energy, economic, and environmental impacts that resulted from the examined energy and environmental policies. Chapter 8 explains the limitation of the methodology and the analysis and Chapter 9 draws conclusions on main findings in China and mentions next steps for consideration to continue advancing this increasingly critical aspect of sustainable planning.